2017
DOI: 10.1021/acs.macromol.6b02280
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the Fragility-Confinement Effect via Low Molecular Weight Cyclic or Ring Polymer Topology

Abstract: We used differential scanning calorimetry and spectroscopic ellipsometry to measure the molecular weight (MW) dependence of bulk fragility (m bulk) and spectroscopic ellipsometry to measure the thickness dependences of the glass transition temperature (T g) and fragility (m) in supported thin films of low MW cyclic or ring polymer. The effects of confinement on T g and m of thin polymer films are important in a range of advanced technology applications, including nanoimprinting. It has previously been shown th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 75 publications
4
48
0
Order By: Relevance
“…These observations of the suppression of the fragility‐confinement effect associated with bottlebrush PS can also be explained by the constrained and aligned molecular configuration of bottlebrushes. A qualitatively similar but quantitatively stronger suppression of m ‐confinement effects was reported by Zhang et al [ 23 ] in low MW cyclic or ring PS; Lan and Torkelson [ 26 ] reported an elimination of m ‐confinement effects within error in dense PS brushes grafted from a substrate.…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…These observations of the suppression of the fragility‐confinement effect associated with bottlebrush PS can also be explained by the constrained and aligned molecular configuration of bottlebrushes. A qualitatively similar but quantitatively stronger suppression of m ‐confinement effects was reported by Zhang et al [ 23 ] in low MW cyclic or ring PS; Lan and Torkelson [ 26 ] reported an elimination of m ‐confinement effects within error in dense PS brushes grafted from a substrate.…”
Section: Resultssupporting
confidence: 81%
“…In comparison with bulk films of the same polymer, thin films of linear, freely deposited polymers that are a few tens of nanometers thick may exhibit significantly different properties, for example, glass transition temperature ( T g ), fragility, and stiffness among others. [ 1–48 ] For instance, in comparison with a bulk polystyrene (PS) film and as measured by ellipsometry, a 21‐nm‐thick, substrate‐supported high molecular weight (MW) PS film exhibits a T g reduction of 10°C. [ 18 ] Understanding such nanoscale T g ‐confinement effects in polymers is important for many advanced technological applications, for example, thin films used in nanolithography processes for microchip manufacturing.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations